Application of digital shearing speckle pattern interferometry for thermal stress. (September 2018) - Wang, X.; Gao, Z.; Yang, S.; Gao, C.; Sun, X.; Wen, X.; Feng, Z.; Wang, S.; Fan, Y.
Highlights: Non-contact, real time and full-field measurement for thermal stress. An easy way to realize the measurement of thermal stress component. New application of improved shearography developed by the authors. Abstract: A thermal stress measuring method based on the digital shearing speckle pattern interferometry (DSSPI) is proposed in this paper. The concept of the method is that the thermal inequality leading to the deformation of the object surface will be recorded by the shearing speckle pattern, which is captured by CCD and analyzed in computer subsequently. This system making use of Wollaston prism has obvious advantages in non-contact, instantaneity, high-efficiency, low-cost, robustness and simplicity. The principle of the method is elucidated, and related experimental results with the simulation of finite element method (FEM) in contrast are presented.